Sensors for Ranging and Imaging - Brooker, Graham (Electromagnetic Waves Ser., 2022)
This comprehensive textbook and reference provides a solid background in active sensing technology, for graduate students studying sensing systems and industry professionals wishing to expand or update their knowledge. This new edition has been comprehensively updated and expanded to include the latest radar technologies.